Comparative analysis reveals gravity is involved in the MIZ1-regulated root hydrotropism. (9th September 2020) - Li, Ying; Yuan, Wei; Li, Luocheng; Dai, Hui; Dang, Xiaolin; Miao, Rui; Baluška, František; Kronzucker, Herbert J; Lu, Congming; Zhang, Jianhua; Xu, Weifeng
Abstract : The divergent roles of gravity in root hydrotropism contribute to the acquisition of water from different directions in a heterogeneous soil environment. Abstract: Hydrotropism is the directed growth of roots toward the water found in the soil. However, mechanisms governing interactions between hydrotropism and gravitropism remain largely unclear. In this study, we found that an air system and an agar–sorbitol system induced only oblique water-potential gradients; an agar–glycerol system induced only vertical water-potential gradients; and a sand system established both oblique and vertical water-potential gradients. We employed obliquely oriented and vertically oriented experimental systems to study hydrotropism in Arabidopsis and tomato plants. Comparative analyses using different hydrotropic systems showed that gravity hindered the ability of roots to search for obliquely oriented water, whilst facilitating roots' search for vertically oriented water. We found that the gravitropism-deficient mutant aux1 showed enhanced hydrotropism in the oblique orientation but impaired root elongation towards water in the vertical orientation. The miz1 mutant exhibited deficient hydrotropism in the oblique orientation but normal root elongation towards water in the vertical orientation. Importantly, in contrast to miz1, the miz1 / aux1 double mutant exhibited hydrotropic bending in the oblique orientation and attenuated root elongation towards water in the vertical orientation. Our results suggest that gravitropism is required for MIZ1-regulated root hydrotropism in both the oblique orientation and the vertical orientation, providing further insight into the role of gravity in root hydrotropism.